D.H. Lawrence, Rananim and Gilbert Cannan’s Windmills - Harrison, Andrew (Oxford University Press, 2018)
Biographers and critics of D. H. Lawrence have long recognized the significance of his various schemes to establish small utopian communities in locations such as Florida, the Andes, Palestine, Connecticut, and New Mexico. Recent accounts have, however, sought to distinguish the so-called ‘Rananim’ fantasy which Lawrence created with his wife and a select group of friends over Christmas and New Year 1914–1915 from his later schemes for communitarian living. This essay offers a detailed and revisionary reassessment of the contexts of the Rananim fantasy, drawing on little-known evidence and a previously overlooked textual source to suggest that the largely forgotten playwright, author and critic Gilbert Cannan shared Lawrence’s anti-war views in this period and actively participated in the formulation of Rananim and the associated plan to inhabit an island in the South Seas.